2005
DOI: 10.1245/aso.2005.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Valosin-Containing Protein (p97) Is Correlated With Disease Recurrence in Follicular Thyroid Cancer

Abstract: The prognostic utility of VCP expression in FTC was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…The current results, demonstrating that the interaction between SIK2 and p97/VCP regulates ERAD, supports the possibility that SIK2, like p97/VCP, may serve as a key regulator in the ubiquitin-proteasome system and autophagy. Furthermore, this regulatory network may have significant implications in cancer biology as previous reports have shown that elevated p97/VCP levels correlate with metastasis of several types of cancers (55)(56)(57)(58) and that SIK2 is required for cancer cell growth (9). Collectively, these observations strengthen the notion that SIK2 is necessary for the proper functions and integrity of the ubiquitin-proteasome system and autophagy, which in turn are critical for cancer cell proliferation and survival.…”
Section: Discussionsupporting
confidence: 67%
“…The current results, demonstrating that the interaction between SIK2 and p97/VCP regulates ERAD, supports the possibility that SIK2, like p97/VCP, may serve as a key regulator in the ubiquitin-proteasome system and autophagy. Furthermore, this regulatory network may have significant implications in cancer biology as previous reports have shown that elevated p97/VCP levels correlate with metastasis of several types of cancers (55)(56)(57)(58) and that SIK2 is required for cancer cell growth (9). Collectively, these observations strengthen the notion that SIK2 is necessary for the proper functions and integrity of the ubiquitin-proteasome system and autophagy, which in turn are critical for cancer cell proliferation and survival.…”
Section: Discussionsupporting
confidence: 67%
“…Recent functional studies have confirmed the significance of the physical interactions [76]. p97 was also known to be overexpressed in multiple cancers [77-83], pointing to a possible addiction [84]. …”
Section: Alternative Paths To Testing the Hypothesis That Cancer Cellmentioning
confidence: 99%
“…In humans, its expression level was found to be elevated in certain types of cancer tissues (Yamamoto et al, 2004a(Yamamoto et al, , 2005. The protein is mainly localized in the cytosol, but a signiWcant fraction is associated with membranes of various organelles such as the endoplasmic reticulum (ER) and the Golgi (Acharya et al, 1995;Latterich et al, 1995;Rabouille et al, 1995).…”
Section: Introductionmentioning
confidence: 99%